Productivity Gap and Asymmetric Trade Relations: The Canada-United States of America Integration Process - Gonzalez, Germán H. (Economia, 2014)
The usefulness of the European model of integration is currently subject to debate and the North American integration process has been largely ignored as a comparative framework. The asymmetrical relationship between Canada and the United States began a long time before NAFTA, and the study of this process could shed light on the usual problems faced by Latin American countries. This article attempts to encourage discussion about this topic. Particularly,there is evidence for a substantial and positive change in Canadian productivity at the time of the Canada-US Free Trade Agreement (CUFTA). However, the enactment of the North American Free Trade Agreement (NAFTA) does not seem to have had the same effect as the earlier treaty.